1985
DOI: 10.1037/0022-3514.49.5.1330
|View full text |Cite
|
Sign up to set email alerts
|

Learned helplessness and judgments of control.

Abstract: One of the central hypotheses of learned helplessness theory is that exposure to noncontingency produces a reduced ability to perceive response-outcome relations (the postulated "cognitive deficit"). To test this hypothesis, subjects were exposed to a typical helplessness induction task and then asked to make judgments of the amount of control their responses exerted over a designated outcome (the onset of a light). Support for the postulated cognitive deficit would be found if subjects who experienced the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
4

Year Published

1987
1987
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
2
12
0
4
Order By: Relevance
“…Consistent with findings of Alloy and Abramson (1982) and Ford and Neale (1985), no support was found for the cognitive deficit of learned helplessness theory. It is possible that present results were obtained because the computer task was a nonsocial activity removed from everyday experience, therefore not influenced by the very social experience of battering.…”
Section: Perceptions Of Controlsupporting
confidence: 89%
“…Consistent with findings of Alloy and Abramson (1982) and Ford and Neale (1985), no support was found for the cognitive deficit of learned helplessness theory. It is possible that present results were obtained because the computer task was a nonsocial activity removed from everyday experience, therefore not influenced by the very social experience of battering.…”
Section: Perceptions Of Controlsupporting
confidence: 89%
“…Ford and Neale (21) point out that if the belief in internal lack of control produced by helplessness persists for a long time, it will lead to an underestimation of control in a highly uncontrollable situation, such as cancer.…”
Section: Discussionmentioning
confidence: 98%
“…This question was posed in the light of two apparently conflicting reports (i.e., Ford & Neale, 1985;Maldonado et al, 1991). The present studies showed, unequivocally, that prior exposure to uncontrollable/noncontingent feedback does have a subsequent detrimental effect on judgements of control.…”
Section: Discussionmentioning
confidence: 98%
“…Ford and Neale (1985) employed two groups of subjects: One group was exposed to a cognitive helplessness induction pretreatment, analogous to that used by Hiroto and Seligman (1975); the other group received no helplessness induction. Both groups were subsequently exposed to judgement of control test tasks with three different levels of predetermined contingency: low (dP = 25%), medium (dP = 50%), and high (dP = 75%).…”
mentioning
confidence: 99%